Organizational Culture and Ethical Leadership Affecting the Personnel Management Effectiveness of Local Administrative Organizations in Si Songkhram District, Nakhon Phanom Province - Phaingoen, Theerawan; Swasthaisong, Sanyasorn; Romyen, Lamai (Interdisciplinary Academic and Research Journal, 2025)
Background and Aims: The personnel management system of the local government organization determines the direction of work. And has a huge impact on the efficiency of the staff’s work who play an important role in organizing various local activities, Therefore, it is very important to study what factors affect the efficiency of personnel management of local government organizations. The purposes of this research included the following: 1) To investigate the level of the organizational culture, the executives’ ethical leadership, and the efficiency of personnel management of the local administrative organizations in Sri Songkhram District, Nakhon Phanom Province, and 2) To examine the influences of the organizational culture and the executives’ ethical leadership on the efficiency of personnel management of the local administrative organizations in Sri Songkhram District, Nakhon Phanom Province. Methodology: The sample group consisted of 181 personnel of the local administrative organizations in Sri Songkhram District, Nakhon Phanom Province. They were obtained through a stratified random sampling method. The questionnaire was used as the tool for data collection, and statistics employed for data analysis incorporated frequency, percentage, standard deviation, and Multiple Regression Analysis. Results: The study revealed these results: 1. The overall organizational culture of the local administrative organizations in Sri Songkhram District, Nakhon Phanom Province, was at a high level. Also, the executives’ ethical leadership in the local administrative organizations, Si Songkhram District, Nakhon Phanom Province, as a whole, was at a high level. Likewise, the efficiency of the personnel management in the local administrative organizations, Sri Songkhram District, Nakhon Phanom Province as a whole, was at a high level. 2. Regarding the variables of the organizational culture, these variables could be used altogether to accurately predict the efficiency level of the personnel management of the local administrative organizations in Si Songkhram District, Nakhon Phanom Province, 84.10% (R2Adj=.841) at the .01 level of statistical significance. Considering the sub-components of all variables of the organizational culture (excluding participation/involvement and unity), the regression coefficients of these cultural variables were found as follows: adaptability (β=.653) and mission (β=.264). About the variable of the executives’ ethical leadership, these variables could be used jointly to correctly predict the efficiency level of the personnel management of local administrative organizations in Sri Songkhram District, Nakhon Phanom Province, 90.70 percent (R2Adj=.907) with statistical significance at the .05 level. When considering the sub-components of the variables of the executives’ ethical leadership (except for the clarification of the roles, taking care of other, and integrity/honesty), their regression coefficients were shown as the following: long-term care (β=.510) justice (β=.154), ethical guidance(β=.153), and power sharing (β=.116). Conclusion: Organizational culture influences the behavior of all personnel. This includes an impact on the organization’s performance and the efficiency of personnel management in local government organizations. Furthermore, ethical leadership is a modern leadership style that is thought to be appropriate for today’s competitive world. Every organization requires leaders who can serve as role models. As a result, organizational culture and ethical leadership of executives are very important to the efficiency of personnel management in local government organizations.